2014
DOI: 10.1097/ccm.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia During Therapeutic Hypothermia Is Associated With Good Neurologic Outcome in Comatose Survivors of Out-of-Hospital Cardiac Arrest*

Abstract: Bradycardia during therapeutic hypothermia was associated with good neurologic outcome at hospital discharge. Our data indicate that bradycardia should not be aggressively treated in this period if mean arterial pressure, lactate clearance, and diuresis are maintained at acceptable levels. Studies, both experimental and clinical, are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 23 publications
4
38
1
4
Order By: Relevance
“…A recent study found an unadjusted association of heart rates ≤60 bpm during TH with favorable neurological outcome at hospital discharge, which was not statistically significant in the adjusted analysis. 21 The present study supports and strengthens the evidence of SB as a prognostic marker of favorable neurological outcome and adds that a strong association to lower 180-day mortality exists. Though the studies have similar findings, the present study provides a larger sample size (234 compared to 111) and stratifies the population by a lower threshold for bradycardia (<50 bpm), cumulated over the time course of hypothermia, which may be a more physiological definition if confirmed in future studies.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study found an unadjusted association of heart rates ≤60 bpm during TH with favorable neurological outcome at hospital discharge, which was not statistically significant in the adjusted analysis. 21 The present study supports and strengthens the evidence of SB as a prognostic marker of favorable neurological outcome and adds that a strong association to lower 180-day mortality exists. Though the studies have similar findings, the present study provides a larger sample size (234 compared to 111) and stratifies the population by a lower threshold for bradycardia (<50 bpm), cumulated over the time course of hypothermia, which may be a more physiological definition if confirmed in future studies.…”
Section: Discussionsupporting
confidence: 89%
“…The impact of temperature control on heart rate lowering may alter outcome differently according to the clinical situation. In out-of-hospital cardiac arrest patients treated with therapeutic hypothermia, bradycardia has been found to be associated with favorable outcome [41].…”
Section: Discussionmentioning
confidence: 99%
“…A heart rate of 34-40 beats per minute is common at goal temperature and generally does not warrant therapy unless associated with hypotension [28]. Some evidence suggests that the presence of bradycardia is associated with favorable outcome [62]. Atropine is generally ineffective in hypothermia-induced bradycardia.…”
Section: Other Physiologic Changes Induced By Hypothermiamentioning
confidence: 99%